ANALISIS FLYPAPER EFFECT PADA BELANJA DESA DI KABUPATEN SIAK - Winda Hartati; Taufeni Taufik (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
The flypaper effect is a economic phenomenon that suggests that a government grant to a recipient municipality increases the level of local public spending more than an increase in local income of an equivalent size. This study aims to analyze flypaper effect of village income, village fund allocation, and fund allocation on village expenditure of village in Siak Districts. Secondary data are used in this research, that is village financial report in 2015-2018. This research uses purposive sampling with sampling method according to certain criteria. This study obtained 361 villages as sample and analyzed by multiple linier regression analysis using SPSS 23.00 program. The result showed that in partial research indicates that village income has not significant influence on the village expenditure. While, village fund allocation and fund allocation have a significant effect to expenditure village. Thus this means that there has been a flypaper effect on village expenditure of village in Siak Regency